Description of Alpheus gallicus, a new deep-water snapping shrimp from Galicia Bank, northeastern Atlantic (Malacostraca, Decapoda, Alpheidae) - Scioli, Justin A.; Anker, Arthur (Zootaxa, 2020)
A new species of the snapping shrimp genus Alpheus Fabricius, 1798 is described based on material from Galicia Bank, an offshore seamount off northwestern Spain. The type series of Alpheus gallicus n. sp. was collected at a depth of 768–785 m, making it one of the deepest occurring snapping shrimps. The new species belongs to the Alpheus macrocheles species group and is morphologically most similar to several deep-water members of this group, viz. A. lentiginosus Anker & Nizinski, 2011, A. platydactylus Coutière, 1897, A. romensky Burukovsky, 1990, as well as to the shallow-water A. macrocheles (Hailstone, 1835). The new species can be distinguished from all of them by some features on the minor cheliped and dactyli of the third to fifth pereiopods. In addition to morphology, DNA barcoding of the COI gene distinguished A. gallicus n. sp. from all related species with available barcode sequences.